MOTIVATION OF BROILER FARMERS TO IMPLEMENT CLOSED HOUSE SYSTEM IN KEBUMEN REGENCY - A., Wafiyah; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the level of broiler farmers motivation in implementing a closed house system and to determine the factors associated with the level of motivation. The research was conducted in Kebumen Regency, from April to June 2021. The location selection used a purposive sampling method, and the determination of respondents was determined by quota sampling as many as 30 people. To find out the factors related to the motivation of broiler farmers in implementing a closed house system, the Spearman Level Correlation Coefficient analysis method was used (Siegel, 1997). The results of this study indicate that the level of farmers motivation is high. The factors that are very significantly related are: knowledge and intensity of communication; The factors that are significantly related are: attitude; while the factors of age, formal education, non-formal education, livestock ownership, family dependents and livestock experience have an unreal relationship with the motivation of farmers in implementing a closed house system. Conclusions: 1) the level of motivation of broiler farmers in implementing a closed house system is included in the strong category, 2) Factors related to the motivation of broiler farmers in implementing a closed house system are knowledge, attitude and intensity of farmer communication. Suggestion: To the officers of the Livestock Service Office to further improve the guidance and counseling for chicken farmers, in order to increase the motivation and insight of farmers in raising broilers.   Key words : counseling, correlation, attitude, knowledge, communication